Does cardiology hold pharmacogenetics to an inconsistent standard? A comparison of evidence among recommendations. (10th September 2018) - Luzum, Jasmine A; Cheung, Jason C
Current guideline recommendations for pharmacogenetic testing for clopidogrel by the American Heart Association/American College of Cardiology (AHA/ACC) contradict the Clinical Pharmacogenetics Implementation Consortium and the US FDA. The AHA/ACC recommends against routine pharmacogenetic testing for clopidogrel because no randomized controlled trials have demonstrated that testing improves patients' outcomes. However the AHA/ACC and the National Comprehensive Cancer Network (NCCN) recommend other pharmacogenetic tests in the absence of randomized controlled trials evidence. Using clopidogrel as a case example, we compared the evidence for other pharmacogenetic tests recommended by the AHA/ACC and NCCN. In patients that received percutaneous coronary intervention, the evidence supporting pharmacogenetic testing for clopidogrel is stronger than other pharmacogenetic tests recommended by the AHA/ACC and NCCN.